Phylogeny of Flabellulidae (Amoebozoa: Leptomyxida) inferred from SSU rDNA sequences of the type strain of Flabellula citata Schaeffer, 1926 and newly isolated strains of marine amoebae - Dyková, Iva; Fiala, Ivan; Pecková, Hana; Dvořáková, Helena (Folia parasitologica, 2008)
New strains of non-vannellid flattened amoebae isolated from fish, an invertebrate and the marine environment were studied together with Flabellula citata Schaeffer, 1926 selected by morphology as a reference strain. The study revealed a paucity of features distinguishing individual strains at the generic level, but clearly evidenced mutual phylogenetic relationships within the assemblage of strains as well as their affiliation to the Leptomyxida. In this study, the SSU rDNA dataset of leptomyxids was expanded and a new branching pattern was presented within this lineage of Amoebozoa. Sequences of three newly introduced strains clustered in close relationship with the type strain of F. citata, the type species of the genus. Three strains, including one resembling Flamella sp., were positioned within a sister-group containing Paraflabellula spp. Results of phylogenetic analysis confirmed doubts of previous authors regarding generic assignment of several Rhizanmoeba and Ripidomnyxa strains.
Keywords: malé podjednotky ribozomu; DNA, Ribosomal; Phylogeny; Molecular Sequence Data; Amoeba; Polymerase Chain Reaction; ribozomální DNA; Fish Diseases; zvířata; Sequence Analysis, DNA; ryby; Fishes; protozoální DNA; sekvence nukleotidů; Ribosome Subunits, Small; Sequence Alignment; polymerázová řetězová reakce; nemoci ryb; sekvenční seřazení; molekulární sekvence - údaje; sekvenční analýza DNA; Animals; DNA, Protozoan; amébiáza; fylogeneze; Base Sequence; Amebiasis